De Novo Basilar Top Aneurysm in an Elderly Patient Treated with Guglielmi Detachable Coils - Fujimoto, Kenta; Kimura, Ryota; Iida, Jun-ichi; Kawaguchi, Shoichiro; Sakaki, Toshisuke; Nakagawa, Hiroyuki; Kichikawa, Kimihiko; Fujita, Toyohisa (American Journal of Neuroradiology, 2005)
Summary: Ruptured de novo aneurysms, compared with the usual subarachnoid hemorrhage, commonly occur in younger patients and are extremely rare in elderly patients. We discuss their etiology and report the case of a ruptured de novo aneurysm in a 77-year-old woman.